A nerve block supply cart and nerve block champions program associated with increased fascia iliaca block use - Joseph R. Brown; Michael Heffler; Peter Alsharif; Brigit Noon; Justin Inman; Eric Bustos; Juliana Wilson; Ryan Tucker (JEM Reports)
Structured Abstract: Background: Ultrasound-guided nerve blocks (UGNBs) are a vital component of a multimodal approach to managing pain in the Emergency Department (ED). However, implementation has not been universally adopted due to their time-consuming nature and provider discomfort with the procedure. Objectives: The primary outcome of this study was to deploy a new UGNB cart and group of nerve block “champions” and evaluate whether the rate of infrainguinal fascia iliaca compartment block (IFICB) use increased in geriatric hip fractures. Secondary outcomes included length of stay in the ED, complications associated with the UGNB and Morphine Equivalents used compared to patients who did not receive the IFICB. Methods: This was a prospective, observational cohort study performed at a single urban, academic site. Inclusion criteria was based on institutional coding of a hip fracture. Each chart was reviewed as to whether the patient received an IFICIB as well as secondary outcomes like ED length of stay (LOS). Finally, the treating physician was surveyed regarding their decision to perform an IFICB. Results: Of the 146 eligible patients, 15.8 % received an IFICB, an increase from 2.6 % in 2019. 55 physicians were enrolled with a 96 % response rate. Commonly cited reasons for not performing the block were controlled pain and lack of training. Of the 23 UGNBs performed, 14 involved a champion. Despite length of time being cited 10.6 % of the time for not performing the IFICB, patients who received a IFICB had a shorter ED LOS. Conclusion: This study showed that the creation of nerve block “champions” and implementation of an UGNB cart was associated with an increase in their utilization of the IFICB.